1966
DOI: 10.1182/blood.v28.6.807.807
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Evolution of Patterns of Erythropoiesis in Polycythemia Vera as Studied by Iron Kinetics

Abstract: 1. Patients with polycythemia vera may be classified according to their erythropoietic pattern. Erythropoiesis is abnormally increased in all classes. Class I is characterized by normal red cell lifespan. Class II is characterized by shortened red cell lifespan; in Class IIa the shortened red cell survival is related to splenic sequestration of RBC; in Class IIb the markedly shortened red cell survival is predominantly related to intramedullary hemolysis. Class III is characterized by extramedullary erythropoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
2

Year Published

1968
1968
1983
1983

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 9 publications
3
5
0
2
Order By: Relevance
“…The fact that there was a good relationship between megakaryocyte volume/ pl and effective platelet production in PV patients and the conformity of this relationship to control subjects suggests that there were no large individual variations in the total volume of erythropoietic marrow in the material analyzed. This is in agreement with the view of Pollycove et al (1966), Van Dyke et al (1968) and Wasserman (1971) that there is a normal skeletal distribution of the erythropoietic marrow in the early state of PV. Most of the patients in the present study were recently diagnosed and had a short duration of the disease (Table I).…”
Section: Discussionsupporting
confidence: 93%
“…The fact that there was a good relationship between megakaryocyte volume/ pl and effective platelet production in PV patients and the conformity of this relationship to control subjects suggests that there were no large individual variations in the total volume of erythropoietic marrow in the material analyzed. This is in agreement with the view of Pollycove et al (1966), Van Dyke et al (1968) and Wasserman (1971) that there is a normal skeletal distribution of the erythropoietic marrow in the early state of PV. Most of the patients in the present study were recently diagnosed and had a short duration of the disease (Table I).…”
Section: Discussionsupporting
confidence: 93%
“…In the 22 cases described here, no correlation was noted between the elevated TRBC and the Hb or PCV. Our data and those of other workers indicate that the plasma volume may be normal, decreased or increased in polycythaemia Vera and this fact accounts for the lack of correlation between PCV and TRBC (Berlin, Lawrence and Gartland, 1950;Szur, Lewis and Goolden, 1959;Verel, 1961 ;Pollycove, Winchell and Lawrence, 1966).…”
Section: Ferrokinetic Sttidiessupporting
confidence: 71%
“…By contrast, the cases reported here have shown features of both PV and MF in a unique relationship which may be referred to as a transitional myeloproliferative disorder (TMPD). Pollycove et al(1966), in a review of ferrokinetic studies on 64 patients with PV, reported that 25 patients had surface counting evidence of extramedullary erythropoiesis in the spleen. In this group of PV patients which they labelled 'Type 111' there was a variable red cell production by the marrow with peripheral blood red cell values often lower than or within the normal range.…”
Section: Discussionmentioning
confidence: 99%